Mesenchymal stem cell application in pulmonary disease treatment with emphasis on their interaction with lung-resident immune cells - Hazrati, Ali; Mirarefin, Seyed Mohamad Javad; Malekpour, Kosar; Rahimi, Arezou; Khosrojerdi, Arezou; Rasouli, Ashkan; Akrami, Susan; Soudi, Sara (Frontiers in Immunology, 2024)
Due to the vital importance of the lungs, lung-related diseases and their control are very important. Severe inflammatory responses mediated by immune cells are among the leading causes of lung tissue pathology and damage during the COVID-19 pandemic. In addition, uncontrolled immune cell responses can lead to lung tissue damage in other infectious and noninfectious diseases. It is essential to control immune responses in a way that leads to homeostasis. Immunosuppressive drugs only suppress inflammatory responses and do not affect the homeostasis of reactions. The therapeutic application of mesenchymal stem cells (MSCs), in addition to restoring immune homeostasis, can promote the regeneration of lung tissue through the production of growth factors and differentiation into lung-related cells. However, the communication between MSCs and immune cells after treatment for pulmonary diseases is essential, and their investigation can help develop a clinical perspective. Different studies in the clinical phase showed that MSCs can reverse fibrosis, increase regeneration, promote airway remodeling, and reduce damage to lung tissue. The proliferation and differentiation potential of MSCs is one of the mechanisms of their therapeutic effects. Also, they can secrete exosomes that affect the function of lung cells and immune cells and change their function. Another important mechanism is that MSCs reduce harmful inflammatory responses through communication with innate and adaptive immune cells, which leads to a shift in the immune system toward regulatory and hemostatic responses.